ANALISIS PENGARUH PENAMBAHAN BAHAN STABILISATOR ABU JERAMI TERHADAP KEPADATAN TANAH LEMPUNG EKSPANSIF KABUPATEN PAMEKASAN - laily endah fatmawati; Herry Widhiarto; Heri Santoso (KURVATEK, 2020)
Expansive clay is a soil that has a low carrying capacity and high shrinkage growth. Tthe soil has certain limited physical and mechanical properties. Therefore a stabilization is needed so that the parametric soils values ​​become better so that they can be used as subgrade in a construction. Tests carried out include, specific gravity testing, liquid limits, plastic limits, and compaction testing with proctor test and CBR test. The soil was used in this study was taken from the area Bujur Timur, Pamekasan. The soil included the CH group with a plasticity index of 43.5%. The percentage of addition of rice straw is 0%, 2%, 4%, 6%, 8%, 10% of the dry weight of the soil. The most optimum of proctor test results are the addition of rice straw ash by 5.8% with 0MC (Optimum Moisture Content) value of 15,20 % and dry content weight 1.72 gr/cm3. The optimum test results with 7.8% rice straw ash with a CBR value of 5.4% so that can be used for alternative soil improvement. Keywords: expansive clay, rice straw ash, soil stabilization, pamekasan